2005
DOI: 10.1111/j.1365-2702.2005.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of work for nursing assistants who stay in long‐term care

Abstract: Nursing assistants provide most of the care to residents of long-term facilities. Understanding their perspective offers insight into nursing administrators in creating environments in which safe, compassionate and cost-effective care co-exist. Implications for clinical practice are framed within King's theory of goal attainment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 18 publications
(20 reference statements)
4
61
0
Order By: Relevance
“…Supervisory support, autonomy, and respect were found to support high commitment levels in long term care (Bishop et al, 2008), and DCWs have expressed that they most desire recognition, respect, rewards, empowerment, and inclusion in decision-making (Bowers et al, 2003;Caspar & O'Rourke, 2008;Leutz et al, 2009;Secrest et al, 2005;Stone, 2004Stone, , 2011. All such leader behaviors are reflected in the five transformational leadership subscales in some fashion, and the study results illustrated the statistically significant relationship between the transformational leadership subscales and overall organizational commitment, affective commitment, and normative commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Supervisory support, autonomy, and respect were found to support high commitment levels in long term care (Bishop et al, 2008), and DCWs have expressed that they most desire recognition, respect, rewards, empowerment, and inclusion in decision-making (Bowers et al, 2003;Caspar & O'Rourke, 2008;Leutz et al, 2009;Secrest et al, 2005;Stone, 2004Stone, , 2011. All such leader behaviors are reflected in the five transformational leadership subscales in some fashion, and the study results illustrated the statistically significant relationship between the transformational leadership subscales and overall organizational commitment, affective commitment, and normative commitment.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Secrest, Iorio, and Martz (2005) confirmed that among the most prominent rewards for facility caregivers were the family-like relationships they experienced with many of their residents and coworkers. Missing from this literature, however, is a clear description of what family experience caregivers may reference when they report such perceptions, and how the memory of past family relationships may enter into their work.…”
Section: Abstract Nursing Home Assisted Living Familymentioning
confidence: 67%
“…This is a vulnerable worker group in which socioeconomic stability is needed. More research should be conducted to develop an infrastructure in which adequate wages and benefits, as well as advancement opportunities, for CNAs are incorporated into the organizational climate (Fowler, 2003;Painter & Kennedy, 2000;Secrest et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the CNA workforce in LTC in relation to staff burnout, the effects of work assignments, staffing patterns, job enrichment, and personal growth opportunities (Burgio, Fisher, Fairchild, Scilley, & Hardin, 2004;Harrington & Swan, 2003;Parsons, Simmons, Penn, & Furlough, 2003;Secrest, Iorio, & Martz, 2005), but few have focused on the actual perceptions of CNAs regarding their work environment. The role of perceptions of the work environment in CNA turnover is unknown because few nursing homes, including those in Iowa, conduct exit interviews with terminating CNAs.…”
Section: Literature Reviewmentioning
confidence: 99%